The Roman Communication Leusinium-Sallunto-Anderba - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This paper presents the data about the Roman road communication Leusinium–Sallunto–Anderba (the present-day village of Panik – the city of Nikšić) with the settlements along the route. From the road station Ad Zizio (the present-day village of Mosko or Ukšići at the village of Ljubomir) the road led east to the road station Leusinium (Panik, near the city of Bileća), then over the road station Sallunto (the village of Riječani – east of Bileća, on the road to Nikšić). From the road station Leusinium, one branch of the road led east to the former Roman castrum Anderba, and another branch led north to the interior of the province of Dalmatia, via the present-day city of Gacko, towards the region of Podrinje. The archaeological finds (the remnants of a Roman settlement, road, fragments of  milestones) from the sites in Panik, Riječani and Nikšić (the southern part of the province of Dalmatia) indicate that his area was, relatively early, connected with the network of Roman road communication. The importance of this branch of the road is testified by the fragments of milestones with inscriptions found in situ. There is no distinctive inscription that could ensure the precise dating of the Leusinium– Sаllunto–Anderba road communication. In addition, no other sources give the details of its construction. It is believed that the Prefect of Dalmatia (14-20 AD), Publius Cornelius Dolabella, started to build the Leusinium–Sаllunto–Anderba road route along which stood the above-mentioned road stations, and that it was completed during the reign of the Emperor Claudius (41-54 AD). Additional reconstructions of this road were most probably conducted in the 3rd and the 4th century, which is testified by the inscriptions mentioned, discovered in the area of Riječani (Nikšić) and Panik (Bileća). We can see that, in narrative and cartographic sources, there is frequently a discrepancy in the data on the road stations and the distance between them. The discrepancy between the information obtained from the historical sources and the finds in archaeological sites has generated a myriad of diverse opinions on these questions.
Keywords: Anderba (Nikšić); Sallunto (Riječani); Leusinium (Panik); southern Dalmatia; Roman communication